The developer's guide to social programming : building social context using Facebook Connect, Google Friend Connect, and the Twitter api. - Hawker, Mark D. (Addison-Wesley Professional, 2010)
In The Developer's Guide to Social Programming , Mark Hawker shows developers how to build applications that integrate with the major social networking sites. Unlike competitive books that focus on a single social media platform, this book covers all three leading platforms: Facebook, OpenSocial, and Twitter. Hawker identifies the characteristics of superior, highly engaging social media applications, and shows how to use the Facebook platform, Google Friend Connect, and the Twitter API to create them. You'll find practical solutions and code for addressing many common social programming challenges, from site registration to search, blog commenting to creating location-based applications. Hawker concludes by walking you through building a complete, integrated social application: one that works seamlessly across all leading platforms, and draws on powerful features from each. Coverage includes Working with the Twitter API, including the Search API, Lists API, and Retweets API Authenticating users with Twitter OAuth Mastering the Facebook API, FQL, and XFBML Utilizing the Facebook JavaScript Library for creating dynamic content, and animation Exploring the Google Friend Connect JavaScript API, and integrating with the OpenSocial API Using Facebook's tools for sharing, social commenting, stream publishing, and live conversation Using the PHP OpenSocial Client Library with Google Friend Connect Creating, testing, and submitting Google Friend Connect gadgets.